The Power of Robots: A Dedication of Computer Science for Human Capitals Management - Nalom Siagian; Jhonson Pasaribu; Theresia Mastiur Ningsing Siagian (Postgraduate, University of Mataram, 2023)
Robotics technology is becoming an increasingly challenging necessity for the next time zone. Humans have even become one with the technology, in various increasingly concrete applications. This study aims to describe and investigate the roles of organizational robots to redesign concepts and theories of human resources management into the new designation of human resources management. This research is a literature review with a qualitative approach that has a descriptive character. Data is taken from various sources that are compatible with this study. The data taken from different books on the related topics, public websites and other statistics, various journals, newspapers and which are collected from them. Considerable information has been gathered and collected from these sources thus allowing for accurate analysis, comparing, accumulation, explanation. The main finding is the organizational robotics have an effect on the most important concepts of theories of the human resources management especially human resources planning, employment, training and performance appraisal system for organizational regulations, finally they have ability to effect of costs, productivity, profitability of company and organizational performance.